Designing and building a business data collection application using the waterfall method - Khwuta , Yoseph Dominikus Da Yen; Londa , Maria Adelvin; Wee, Yohanes Ardianus (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2023)
The Department of Industry and Trade of Ende Regency is a local government agency that is directly related to the process of data collection and assistance for small and medium industrial enterprises (SME) in Ende Regency which is still done manually, causing problems in data collection. the process is considered to be very slow so there is still a lot of SMI data that is not recorded clearly and completely. This website-based IKM data collection application aims to assist the Trade and Industry Office of the Ende Regency in the computerized IKM data collection process and checking of business assistance funds so that it can run effectively and efficiently. The software design methodology used in this study is the system development life cycle (SDLC) starting from the analysis, design, implementation, testing, and maintenance stages. In this study, researchers used 2 system testing methods, namely system usability scale testing (SUS), and black box testing. The results of the research on 4 respondents obtained an average SUS score of 86.2 with an acceptable interpretation of the B value category. While the results of black box testing are obtained from the tests that have been carried out, it can be concluded that all functional features can run well.